Minimizing the Consumption of Working Time when Machining the Connecting Rod by Optimizing the Machine Tool" - Khamidulla, Isakhanov; Shukhratkizi, Akramova Komila (International Journal of Human Computing Studies, 2022)
This article contains general information about the connecting rods, its structure, methods of obtaining. Also, the calculation of the machine tool for milling the connecting rod flats was made.